Culture of Litopenaeus vannamei in Relation to Water Quality, Production and Management in Kunak, Sabah - Nor Anggeriani, Binti Arsad (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This study was conducted in Kunak, Sabah. The objectives of this study were to document the water quality at the culture ponds, to estimate the growth rate and feed conversion ratio of Litopenaeus vannamei and to propose proper management of Litopenaeus vannamei culture in the study area. Sampling work were done twice; first on 18th - 19th Oct 2013 while the second was on 11th - 12th Feb 2014. Water quality parameters for five culture ponds with different age of culture and reservoir were analysed and compared based on the duration of culture period. The in-situ parameters such as dissolved oxygen (DO), pH and temperature were recorded every two hours in each pond. DO showed great fluctuation in pond with 90 days culture period and uniform pattern in pH and temperature were recorded for pond with one day culture period. The turbidity, total suspended solids (TSS) and biochemical oxygen demand (BOD5) were higher in Pond Days 90th culture period pond. The FCR for shrimp pond culture in Kunak ranged from 1.27 to 1.46 with a mean 1.365. Several management procedures to be taken for sustainable the shrimp culture in Kunak is also proposed.